Calonectria leaf blight of Eucalyptus: A global review. (19th August 2022) - Bose, Ratnaboli; Banerjee, Sabyasachi; Pandey, Amit; Bhandari, Maneesh S.; Barthwal, Santan; Pandey, Shailesh
Abstract: Calonectria (= Cylindrocladium ), an internationally recognised fungal ascomycete genus, causes significant diseases on numerous crops of forestry, horticultural and agricultural interest. Eucalyptus, an economically important multipurpose plantation forestry species, is severely threatened by Calonectria leaf blight (CLB) disease in Brazil, Australia, China, Indonesia, Vietnam and India. The disease causes serious mortality in the nurseries/plantations and yield losses due to defoliation. Since the first report of Calonectria in 1867, efforts have been made for the identification and characterisation of this vastly diverse hypocrealean genus. Currently, the genus Calonectria harbours 131 species grouped within 11 species complexes, and broadly categorised into the Prolate and Sphaero‐Naviculate groups. Globally, 35 Calonectria species distributed in seven species complexes cause CLB of Eucalyptus, out of which 29 belong to the Prolate group and five to the Sphaero‐Naviculate group. Likewise, 28 Calonectria species distributed in eight species complexes have been reported in association with infected Eucalyptus tissues and plantation soil, however, their pathogenicity remains to be determined. Given the importance of CLB of Eucalyptus, this review compiles its global impact, shifts in taxonomy and nomenclature of Calonectria, pathogenesis mechanism, defence response of Eucalyptus upon infection and disease management. This study identifies and provides direction to crucial areas of future research on CLB which is severely impacting Eucalyptus plantations globally. Abstract : Eucalyptus, an economically important multipurpose plantation forestry species, is severely threatened by Calonectria leaf blight (CLB) disease in Brazil, Australia, China, Indonesia, Vietnam and India. Given the importance of CLB of Eucalyptus, this review compiles its global impact, shifts in taxonomy and nomenclature of Calonectria, pathogenesis mechanism, defence response of Eucalyptus upon infection, and disease management. This study identifies and provides direction to crucial areas of future research on CLB which is severely impacting Eucalyptus plantations globally.